A Retrospective View of Discourse-Historical Approach (DHA) - Jiin Yih, Yeo; Su Hie, Ting; Collin, Jerome; Hugh John, Leong (Universiti Teknologi MARA Cawangan Pahang., 2025)
The paper provides a retrospective view of the discourse-historical approach (DHA) by conducting a bibliometric analysis of articles on DHA in the Scopus database for 2002-2023. A total of 335 documents were retrieved, indicating that the field remains relatively new and unsaturated. The United Kingdom was the leading contributor to DHA research because the founder of DHA, Ruth Wodak is from Lancaster University. The focal point of DHA research has been on media and political discourse because of the research interests of Wodak and her former postgraduate students, Boukala and Forchtner, who published prolifically on DHA. However, the most globally cited work is Baker et al.‘s (2008) ―A useful methodological synergy? Combining critical discourse analysis and corpus linguistics to examine discourses of refugees and asylum seekers in the UK press‖. The bibliometric analysis showed that the Journal of Language and Politics has the most publications on DHA while Discourse and Society has the highest total citations. DHA research since 2017 has gravitated towards analysis of ―argumentation‖ in populism, ideology and COVID-19 in social media discourse, and there is an emergence of research focusing on the nomination and predication strategies in new areas such as interpretation and Islamophobia. The study indicates that selectivity in the use of discursive strategies may hamper the potential of DHA to explain how societal changes influence discourse, and for the field to advance, it is essential to revisit a comprehensive framework that necessitates an examination of all five discursive strategies.